Molecular survey of Besnoitia spp. (Apicomplexa) in faeces from European wild mesocarnivores in Spain. Issue 6 (7th July 2021) - González‐Barrio, David; Köster, Pamela C.; Habela, Miguel A.; Martín‐Pérez, Manuel; Fernández‐García, Jose L.; Balseiro, Ana; Barral, Marta; Nájera, Fernando; Figueiredo, Ana M.; Palacios, Maria Jesus; Mateo, Marta; Carmena, David; et al.
Abstract: Numerous studies have unsuccessfully tried to unravel the definitive host of the coccidian parasite Besnoitia besnoiti . Cattle infections by B. besnoiti cause a chronic and debilitating condition called bovine besnoitiosis that has emerged in Europe during the last two decades, mainly due to limitations in its control associated with the absence of vaccines and therapeutical tools. Although the exact transmission pathways of B. besnoiti is currently unknown, it is assumed that the parasite might have an indirect life cycle with a carnivore as definitive host. Current lack of studies in wildlife might underestimate the importance of free‐living species in the epidemiology of B. besnoiti . Thus, the aim of the present study is to assess the presence of Besnoitia spp. in free‐ranging mesocarnivores in Spain. DNA was searched by PCR on faeces collected from wild carnivores as a first approach to determine which species could be considered as potential definitive host candidates in further research. For this purpose, a total of 352 faecal samples from 12 free‐living wild carnivore species belonging to the Canidae, Felidae, Herpestidae, Mustelidae, Procyonidae and Viverridae families were collected in seven Spanish regions. PCR testing showed that Besnoitia spp. DNA was present in four faecal samples from red foxes collected in western Spain, an area with the greatest density of extensively reared cattle and associated with high incidence of bovine besnoitiosis in the country. To date, this is the first report of a B. besnoiti ‐like sequence (99.57% homology) from carnivore faeces in a worldwide context. Red foxes might contribute to the epidemiology of B. besnoiti, although further studies, mostly based on bioassay, would be needed to elucidate the accuracy and extent of these interesting findings.